Identifying Factors to Measure Managerial and Leadership Competence of Business School Educated Managers - Shaikh, Ahmed; Bisschoff, Christo A.; Botha, Christoff J. (International Review of Management and Marketing, 2017)
The article explores a model to measure managerial and leadership competence of business school educated managers by seeking to identify the latent variables in the model. Here the research uses exploratory factor analysis to identify latent variables. The article also renders a verdict on the validity of the model as a higher objective of model development. In total 385 questionnaires using a five-point Likert scale were independently administered to business school educated managers; 94% responded. Exploratory factor analysis identified five factors explaining a cumulative variance of 56.5%. These are Leadership skills, Managerial challenges, Emotional intelligence, Personal value system, and Cultural sensitivity. Measuring criteria with low factor loadings or those with high dual-loadings were eliminated in the purification of the measuring criteria. The data have a high reliability coefficient of 0.947 while the constructs also adhered to the validity requirements. The research is of value to managers who aim to improve their managerial and leadership skills after studying advanced management programmes at business schools, employees of such educated managers and also to academia aiming to explore this avenue of managerial and leadership skills development further. Keywords: Management, leadership, competencies, validity, measurement, model, factors. JEL Classifications: A23, I23, M19